Pengenalan Tentang Gambut, Fungsi, Kerusakan, dan Upaya Pemulihannya di SMAN 2 Kahayan Tengah Desa Bukit Rawi Kabupaten Pulang Pisau Provinsi Kalimantan Tengah - Nomeritae; Allan Restu Jaya; Hendro Suyanto; I Made Kamiana; Raden Haryo Saputra; Haiki Mart Yupi; Dwi Anung Nindito (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2023)
Central Kalimantan Province is an area with a very large area and potential for peatland utilisation, but faces various environmental problems that have been going on for more than two decades. Environmental education about peat is one of the important factors to minimise environmental damage. Therefore, an explanation of peatlands and their problems and recovery efforts needs to be given to the community, including in this case the students of SMAN 2 Kahayan Tengah, Bukit Rawi Village, Pulang Pisau Regency, Central Kalimantan Province, as a form of additional useful knowledge, so that students can better understand and understand and can participate and care more about the environment in their area, which also has peatland characteristics, so that peatlands can be preserved. The method used was in the form of presentations, lectures and discussions. The conclusion of this community service programme is that with the explanation given, students' understanding of peatland has increased, with the hope that the students will be able to have a positive impact on the community and the environment around them.